Chromosome studies in Hippeastrum (Amaryllidaceae): variation in genome size - Poggio, Lidia (2007)
This paper presents the karyotype and DNA content of 12 diploid species of Hippeastrum from South America. The variation in genome size is compared with the karyotype and DNA content of Amaryllis belladonna from South Africa. The Hippeastrum species present a uniform and bimodal basic karyotype formula, but significant differences are found in the total chromosome volume (TCV) and nuclear DNA content. A positive correlation between the DNA content and TCV is also observed. The karyotype's constancy is a product of changes in DNA content occurring in the whole chromosome complement. The DNA addition to the long and short sets of chromosomes varies independently. In species with higher DNA contents, the short chromosomes add equal DNA amounts to both arms, maintaining their metacentric morphology, whereas the long chromosomes add DNA only to the short arm, increasing the chromosome symmetry. These data show that the evolutionary changes in DNA amount are proportional to chromosome length, maintaining the karyotypic uniformity. A. belladonna has a larger DNA content and possesses a karyotype different from that of Hippeastrum spp., supporting the distinction between the two genera and upholding the name Amaryllis for the South African entity against Hippeastrum for the South American genus.